Human cytomegalovirus and Epstein–Barr virus infections occurring early after transplantation are risk factors for antibody-mediated rejection in heart transplant recipients - Saldan, Alda; Mengoli, Carlo; Sgarabotto, Dino; Fedrigo, Marny; Angelini, Annalisa; Feltrin, Giuseppe; Gambino, Antonio; Gerosa, Gino; Barzon, Luisa; Abate, Davide (Frontiers in Immunology, 2023)
Background. Antibody-mediated rejection (AMR) is a serious complication affecting the survival of patients receiving transplantation. Human cytomegalovirus (CMV) and Epstein–Barr virus (EBV) are common viral infections that occur after transplantation, frequently emerging as viral reactivation in donor grafts or transplant recipients. The present study aimed to investigate the association between CMV and EBV infections and early-onset AMR. Materials and methods. This study was conducted at the Heart Transplantation Center of Padova General Hospital and included a cohort of 47 heart transplant recipients (HTxs), including 24 HTxs diagnosed with AMR and 23 control HTxs with no episodes of AMR. Only early cases of CMV and/or EBV infections (1–90 days after transplantation) were considered. The Fisher’s exact test and logistic regression analysis were used to statistically analyze the correlation and association between AMR and CMV or EBV infection. Results. We observed a positive statistical association between CMV and EBV infections (two-sided Fisher’s exact test, p = 0.0136) and between EBV infection and AMR (two-sided Fisher’s exact test, p = 0.0034). Logistic regression analysis revealed a direct statistical association between CMV and EBV infections and AMR risk (p = 0.037 and 0.006 and odds ratio = 1.72 and 2.19, respectively). AMR occurrence was associated with increased viral loads of both CMV and EBV early after transplantation. Discussion. These findings suggest the role of CMV and EBV infections as relevant risk factors for AMR in HTxs for the first time.